Three-level Z-source hybrid direct AC-AC power converter topology - Effah, Francis Boafo (2014)
Voltage source inverter (VSI) is the traditional power converter used to provide variable voltage and frequency from a fixed voltage supply for adjustable speed drive and many other applications. However, the maximum ac output voltage that can be synthesized by a VSI is limited to the available dc-link voltage.